A diferenciada construção da personagem em Eça de Queiroz & Trindade Coelho: singularidades de uma rapariga loura e Manuel Maçores - Leão, Flavia Regina Oliveira (2007)
This dissertative work promotes a stylistic-literary approach between two short stories from the Portuguese Literature, from the nineteenth century  Singularidades de uma rapariga loura, by Eça de Queiroz, and Manuel Maçores, by Trindade Coelho  through the comparative description of the construction of their characters. As they are transitory and transitive between two realities, the romantic and the realistic, we have defined our objectives which consists of differentiating the treatement that is dedicated to them, based on the ficcional techniques used by their respective narrators in their ficccional projects: the manking and the unmasking. In particular, we analyse the role of the transformation of the indirect speech into the direct one, and the lexical choice as a complementary technique, keeping in mind that this analysis led us to the reading of alternatives in the critical space of the relation narrator and character. In the first chapter, studies of Ernesto Da Cal, Wayne Booth, Mikhail Bakhtin and Jean Starobinski, among others, assisted us in presenting the narrator-character discursive play, in Singularidades de uma rapariga loura, short story that keeps in itself the complexity of the structure between being and seeming in the ficcional context in discursive revelation. In the second chapter, we resort to Segolin s contemporary studies, in order to prove the autonomy that the character achieves by means of narrating technique, in Manuel Maçores, a handmade work which revealed the transitivity of the character from Romantism to Realism, by using the critical space in the narrative setting. In the third chapter, with theoretical supporters as Lukács and Barthes, we deal with the differentiation of the language in the composition of the Portuguese realistic short story that favored the drawing of a parallel between the transitive characters in Singularidades de uma rapariga loura and Manuel Maçores. We conclude, therefore, that the operational variations occured in the narrator-character s distance provoke a diversion in the characters voices in a perspective that takes the tale to the platform of a potential educational novel, under a methodological dominance in the act of permutation, which we believe that contributes to a higher level of social singularity of the Portuguese short story in a historical moment of transformation